Kiloparsec-scale jet-driven feedback in AGN probed by highly ionized gas: A MUSE/VLT perspective. Issue Volume 15:Issue S359(2020) (March 2019) - Rodríguez-Ardila, A.; Fonseca-Faria, M. A.
Abstract: We employ optical spectroscopy from the Multi Unit Spectroscopic Explorer (MUSE) combined with X-ray and radio data to study the highly-ionized gas (HIG) phase of the feedback in a sample of five local nearby Active Galactic Nuclei (AGN). Thanks to the superb field of view and sensitivity of MUSE, we found that the HIG, traced by the coronal line [Fe vii] λ6089, extends to scales not seen before, from 700 pc in Circinus and up to ∼2 kpc in NGC 5728 and NGC 3393. The gas morphology is complex, following closely the radio jet and the X-ray emission. Emission line ratios suggest gas excitation by shocks produced by the passage of the radio jet. This scenario is further supported by the physical conditions derived for the HIG, stressing the importance of the mechanical feedback in AGN with low-power radio jets.